Physical development of students of teacher training college as a result of exercises of cheerleading - I. P. Maslyak; N. V. Krivoruchko (Physical Education of Students, 2016)
Purpose: to define the extent of influence of exercises of cheerleading on physical development of students of teacher training college. Material: researches were conducted on the basis of training college of Kharkov humanitarian teacher training college. 385 students of the I-III courses of not a sports profile took part in them from whom 3 control and 3 experimental groups were created. Results: the level of physical development on indicators of a harmony of a constitution, functionality of the system of breath and resistance of an organism to the hypoxemic phenomena, regulation of the cardiovascular system is determined; the age distinctions on the studied indicators are considered; the positive influence of exercises of cheerleading on indicators of functionality of the system of breath and resistance of an organism to the hypoxemic phenomena, regulation of the cardiovascular system is revealed. Conclusions: 1. As a result of the primary research the "low" level of physical development of students of 15-17 years old is established. 2. The application of exercises of cheerleading in the course of physical training positively wagged on the level of physical development of students of teacher training college.